Selection of Village Community Institutions Siyasah Dusturiyah Perspective - Widya Anggriani D; Abdul Kadir (Al-Balad: Journal of Constitutional Law, 2021)
Election of Village Social Institutions (RT) is a community institution whose election has been regulated in Law, Regional Regulation. The selection process for this social institution is only the village government which plays a role in the selection of the Village Community Institution (RT) and the community is not involved in the process of selecting the Village Community Institution (RT). This type of research is juridical empirical. The approach used is the Sociological Juridical approach. The sampling method used was accidental sampling in non-probability sampling. The data used were primary in the form of interviews and documentation and secondary data in the form of scientific books, theses, research reports and journals. The selection of Village Community Institutions (RT) in Article 3 Paragraph 1 of Permendagri Number 18 of 2018 concerning Village Community Institutions and Village Traditional Institutions has not been carried out because the election process is only carried out by the government, namely the village government does not involve the community in the election of the Head of this RT. The Implementation of Village Community Institution (RT) Election Is Not In Accordance With The View Of Fiqh Siyasah Dusturiyah because in Fiqh Siyasah Dusturiyah every decision-making process in all social affairs is carried out through consensus and consultation with all parties. The Implementation of Village Community Institution (RT) Election Is Not In Accordance With The View Of Fiqh Siyasah Dusturiyah because in Fiqh Siyasah Dusturiyah because every decision-making process in all social affairs is carried out through consensus and consultation with all parties. Inhibiting Factors in the Selection of Village Social Institutions is when the community is given the right to vote in the election of the Village community institution (RT) it is feared that it is not appropriate because when the election for the head of the RT it turns out that Se Lingungan RT still has family ties so he won this election because of his family, even though it was the chairman of the RT. RT is not in accordance with the wishes of the community. The Implementation of Village Community Institution (RT) Election Is Not In Accordance With The View Of Fiqh Siyasah Dusturiyah because in Fiqh Siyasah Dusturiyah because every decision-making process in all social affairs is carried out through consensus and consultation with all parties.